High Incidence of Distant Metastasis Is Associated With Histopathological Subtype of Pediatric Papillary Thyroid Cancer - a Retrospective Analysis Based on SEER - Zeng, Xue; Wang, Zhihong; Gui, Zhiqiang; Xiang, Jingzhe; Cao, Mengsu; Sun, Wei; He, Liang; Dong, Wenwu; Huang, Jiapeng; Zhang, Dalin; Lv, Chengzhou; Zhang, Ting; et al. (Frontiers in Endocrinology, 2021)
Objective Children with papillary thyroid cancer (PTC) have a higher invasive rate and distant metastasis rate, but the mortality rate is lower with unknown reasons. The majority of PTC cases comprise classical papillary thyroid carcinoma (CPTC) and follicular variant papillary thyroid carcinoma (FVPTC). This study aimed to determine the relationship between histopathological subtype and rate of distant metastasis and investigate factors influencing distant metastasis in pediatric PTC. Methods A total of 102,981 PTC patients were recruited from SEER registry, 2004-2015. Proportion of distant metastasis between children (≤18 years) and adults with different histopathological subtypes was compared by propensity score matching. The cut-off age for distant metastasis in children was calculated by receiver operating characteristic (ROC) curve, and the risk factors for distant metastasis in pediatric patients were analyzed by logistic regression models. Results Among the 1,484 children and 101,497 adults included in the study, the incidence of CPTC patients with distant metastasis in children was higher than that in adults (p<0.001). The ROC curve was calculated, which yielded a cut-off age for distant metastasis in CPTC children as 16 years old. In CPTC, the proportion of young children (2-16 years) with distant metastasis was higher than that of adolescents (17-18 years) and adults (>18 years) (both p<0.001). While there was no such trend in FVPTC. In young children (2-16 years), the incidence of CPTC with distant metastasis was higher than FVPTC (p=0.006). There was no difference between the proportion of CPTC and FVPTC with distant metastasis in adolescents (17-18 years) and adults. Logistic regression models revealed that extrathyroidal extension, lymph node metastasis and CPTC histopathological subtype were risk factors for distant metastasis in young children aged 2 -16 years. Conclusions In CPTC, the incidence of distant metastasis in young children (2-16 years) was significantly higher than that in adolescents (17-18 years) and adults (>18 years). In patients with distant metastasis aged 2-16 years, the proportion of CPTC was higer than that of FVPTC. Extrathyroidal extension, lymph node metastasis, and CPTC histopathological subtype were risk factors for distant metastasis in young children aged 2-16 years.